Unshadowing the Stories of Yesterday’s Failed Battle of Let Examinees - Olvina, Bernardo Jr.; Basadre, Kimberly Casssandra; Penarejo, Roshell; Ngo, Cristy Grace (CV. Tripe Konsultan, 2024)
This phenomenological study aimed to unshadow the failed experiences of the Licensure Examinations for Teachers (LET) examinees, how the examinees cope with the failed experience during the LET, and the insights they have on their experience. The study utilized a qualitative design using a descriptive phenomenology approach, with ten failed LET examinees selected through snowball sampling. The researchers used Colaizzi’s Method of Data Analysis as a data analysis tool. The results revealed that the experiences of failed LET examinees are associated with themes such as Time Management, Unpreparedness, Learning Environment, and The Effect of the Support System. Moreover, the study revealed the coping mechanism of failed LET examinees with the themes: Negative Reinforcement, Diverting attention to other things, and Good Support. Furthermore, the failed LET examinee’s insights showed the themes: Setting goals, Health and Expectations, and Integration of Optimism and Pessimism. The analyzed findings of this study unveil the various experiences encountered by the failed LET examinees and how they cope. Thus, this study contributes significant knowledge to examinees who will take the LET in the future and will retake the LET.